Investigation into the hydrodynamic processes of fitting connections for determining pressure losses of transport hydraulic drive - Karpenko, Mykola; Bogdevičius, Marijonas (Transport, 2020)
The article presents the findings of theoretical and experimental research on hydraulic processes occurring in the hydraulic drives of transport machines. The paper analyses the influence of hydrodynamic processes on the flow characteristics of fluid considering different hydraulic fitting connections. The performed analysis is based on numerical simulations using Navier–Stokes equations for the velocity field. The dynamics of fluid flow in the hydraulic system has been investigated taking into account the main parameters like system flow rate in the range of 5 to 100 L/min, the diameter of the pipeline making 1/2” and fitting standards DKOL, ORFS, BSP and JIS. As a result, pressure drop, power losses, resistance and flow coefficients at different fitting connections have been obtained. The article compares the provided results with the findings given employing the calculation method for the standard of equivalent length fitting. To simulate fluid flow, a mesh independence study and turbulence calculations have been performed. Simulation results have been examined conducting physical experiments on measuring pressure losses. Each experimental research includes three measurements of connections bearing in mind each fitting standard.